2022
DOI: 10.1186/s12935-022-02582-2
|View full text |Cite
|
Sign up to set email alerts
|

MiR-129-5p exerts Wnt signaling-dependent tumor-suppressive functions in hepatocellular carcinoma by directly targeting hepatoma-derived growth factor HDGF

Abstract: Background In hepatocellular carcinoma (HCC), histone deacetylases (HDACs) are frequently overexpressed. This results in chromatin compaction and silencing of tumor-relevant genes and microRNAs. Modulation of microRNA expression is a potential treatment option for HCC. Therefore, we aimed to characterize the epigenetically regulated miR-129-5p regarding its functional effects and target genes to understand its relevance for HCC tumorigenesis. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 59 publications
0
9
0
Order By: Relevance
“…In pancreatic stellate cell (PSC), HIF-1α can induce the expression of HDGF and the increased level of HDGF shows anti-apoptotic and pro-fibrotic effects, which can maintain tumor lesions [238]. Interestingly, HDGF was more commonly found to regulate Wnt/β-catenin pathway than autophagy in cancer cells [239][240][241][242]. The expression of Wnt/β-catenin pathway genes was increased in the xenograft model of primary non-small cell lung cancer (NSCLC), while Wnt/β-catenin pathway genes were significantly down-regulated after anti-HDGF treatment, especially Wnt1 and FZD were severely inhibited.…”
Section: Regulatory Pathways For Gemcitabinementioning
confidence: 99%
“…In pancreatic stellate cell (PSC), HIF-1α can induce the expression of HDGF and the increased level of HDGF shows anti-apoptotic and pro-fibrotic effects, which can maintain tumor lesions [238]. Interestingly, HDGF was more commonly found to regulate Wnt/β-catenin pathway than autophagy in cancer cells [239][240][241][242]. The expression of Wnt/β-catenin pathway genes was increased in the xenograft model of primary non-small cell lung cancer (NSCLC), while Wnt/β-catenin pathway genes were significantly down-regulated after anti-HDGF treatment, especially Wnt1 and FZD were severely inhibited.…”
Section: Regulatory Pathways For Gemcitabinementioning
confidence: 99%
“…As a third explanation, harmful oxygen radicals are produced. Reactive oxygen species (ROS) that are iron-related cause DNA damage and DNA strand break in cells when asbestos fibers are inhaled ( 23 ). A persistent kinase-mediated signaling mechanism is the fourth.…”
Section: Pathogenesismentioning
confidence: 99%
“…This kind of gene expression control falls within epigenetic mechanisms. Huge et al [46] observed that in cultured HCC cell lines (HuH7, HepG2 and Hep3B), HDAC inhibition induced the expression of miR-129-5p. Notably, miR-129-5p downregulation is often observed in solid tumors such as HCC [57].…”
Section: Mirnasmentioning
confidence: 99%